Effectiveness of the National Youth Service Corps Scheme Among 2012-2013 Corps Members in Lagos and Oyo States, Nigeria (2015)
The Nigerian government in 1973 established the National Youth Service Corps (NYSC) Scheme as one of the reconstruction programmes to combat the devastating effect of the 1967-1970 civil war. Research efforts had been mainly on job commitment of NYSC officials and criticism about the operators and operation of the Scheme. Though, these have led to some reforms, there is a little information on stakeholders‟ perceived effectiveness of the Scheme. This study examined the effectiveness of the Scheme in relation to its objectives, inculcation of a tradition of industry, skills acquisition and development of sense of national unity, as well as the awareness of the Scheme‟s objectives among the 2012-2013 corps members in Lagos and Oyo States, Nigeria. The study adopted survey design. Multi-stage sampling technique was employed. Three Local Government Areas were randomly selected from each of the two States. Through the proportional random sampling technique, 499 and 353 corps members; 85 and 65 employers of corps members; 22 and 11 NYSC officials from 2012-2013 were selected from Lagos and Oyo States. The five instruments used were: Stakeholder‟s Attitude Towards NYSC Questionnaire (r=0.70), NYSC Employers‟ Programme Evaluation Rating Scale (r=0.85), Corp Members‟ Knowledge of the Scheme Test (KR-20=0.82), and Support Services Information Profile Inventory. Key Informant Interview sessions were also held with nine corps members, nine employers and nine NYSC officials in each State. Seven research questions were answered and three hypotheses were tested at p=0.05. Data were analysed using descriptive statistics, t-test, multiple regression and content analysis. In both States, a large number of corps members (92.9%) were first degree and higher national diploma holders, 7.1% held higher degrees. There were 56.6% male and 43.4% female, with a mean age of 24 years. Inculcation of a tradition of industry in corps members was 66.7%, skills acquisition 50.1% and development of sense of national unity was 41.7%. Their knowledge of Scheme‟s objectives was 74.7%. There was no significant difference between corps members‟ performance as rated by their employers and between corps members‟ exhibiting attributes of industry in Lagos and Oyo States. Training factors, availability of materials, stakeholders‟ qualifications and supervision jointly contributed to the inculcation of a tradition of industry (AdjR2=0.667, F(4.15)=6.435), acquisition of skills for self-employment (AdjR2=0.501, F(4.15)=64.418), and unification (AdjR2=0.417, F(4.15)=4.375). There were insufficient materials for vocational training; skills mostly acquired were photography, ICT training, fumigation-horticulture and artistry. Weak enforcement of enabling legislations was considered a hindrance to full implementation of the Scheme. In both States, majority of the stakeholders believed that the Scheme has contributed meaningfully to the inculcation of a tradition of industry and fostering of patriotism among corps members. The National Youth Service Corps‟ core objectives have been fairly realised among the 2012-2013 corps members in Lagos and Oyo States, with little hindrances to its implementation. Enforcement of existing laws governing the Scheme needs to be strengthened and adequate materials needed to be provided to ensure full realisation of the Scheme‟s objectives.